USING VISUAL AIDS TO ENHANCE VOCABULARY ACQUISITION IN FRENCH AS A FOREIGN LANGUAGE - Narzulloyeva Dilfuza Bahriddin qizi (TADQIQOTLAR, 2025)
Abstract: This article examines the effectiveness of using visual aids in teaching French as a foreign language in increasing vocabulary. The study was conducted with A1 level learners and analyzed the role of pictures, icons, charts, and other visual materials in memorizing new words, using them in context, and developing active vocabulary. The article compares the results of the experimental and control groups, proving that visual aids can increase motivation and enhance efficiency in the learning process.